2002
DOI: 10.1016/s0002-9440(10)64267-8
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Pathology and Sperm Physiology in Acid Sphingomyelinase-Deficient Mice

Abstract: Types A and B Niemann-Pick disease (NPD) are lysosomal storage disorders resulting from the deficient activity of acid sphingomyelinase (ASM). In this manuscript we report the pathobiology of male gonadal tissue and sperm in a knockout mouse model of NPD and demonstrate the importance of ASM for normal sperm maturation and function. Characteristic lipid-filled vacuoles were evident in light micrographs of testis' seminiferous tubules and epithelial cells lining the epididymis of ؊/؊ mice. Electron micrographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 49 publications
(48 reference statements)
8
59
0
3
Order By: Relevance
“…However, oil-red O staining of the LXR / animals did reveal that lipidic inclusions are present within the caput epithelium, suggesting that lipidic transfer systems are impaired in the transgenic animals. In a similar way to that observed in the RXR knockout model, lipid metabolism was found to be impaired in the epididymis of mice deficient for apoB gene expression (Huang et al 1996), apoER2 gene expression (Andersen et al 2003) or the acid sphingomyelinase gene (Butler et al 2002). ApoB, apo E and apoER2 (receptor 2 of apolipoprotein E) genes encode proteins that, together with ATP-binding cassette (ABC) transporters, are involved in the cellular export of cholesterol.…”
Section: Figuresupporting
confidence: 58%
“…However, oil-red O staining of the LXR / animals did reveal that lipidic inclusions are present within the caput epithelium, suggesting that lipidic transfer systems are impaired in the transgenic animals. In a similar way to that observed in the RXR knockout model, lipid metabolism was found to be impaired in the epididymis of mice deficient for apoB gene expression (Huang et al 1996), apoER2 gene expression (Andersen et al 2003) or the acid sphingomyelinase gene (Butler et al 2002). ApoB, apo E and apoER2 (receptor 2 of apolipoprotein E) genes encode proteins that, together with ATP-binding cassette (ABC) transporters, are involved in the cellular export of cholesterol.…”
Section: Figuresupporting
confidence: 58%
“…Sperm with defective cell volume decrease fail to counteract water influx when released into hypo-osmotic conditions, causing cell swelling and coiling of the tail. The swelling is relieved upon perforation of the sperm membrane with detergents, resulting in tail straightness (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, heterozygosity for the apoB gene defect (45) or homozygous deletion of the acid sphingomyelinase gene (21) affects the lipid metabolism of the epididymis and the spermatozoa, resulting in sperm immotility. In particular, the latter model exhibits close resemblance to apoER2-deficient mice inasmuch as the sperm are characterized by detergent-reversible tail angulation (21). Unfortunately, no information is available on the expression of PHGPx protein in this mouse model.…”
Section: Figmentioning
confidence: 99%
“…Types A and B are caused by deficient acid sphingomyelinase activity (Levran et al, 1991), and type C is caused by mutations in NPC1, a gene thought to be involved in intracellular trafficking of cholesterol (Carstea et al, 1997). Mouse models of related lipid storage disorders such as Tay-Sachs disease also exhibit reproductive impairment (Trasler et al, 1998), and recent studies of the ASMKO line revealed defects in sperm physiology attributable to lipid-filled vacuoles present in the testis and epididymis (Butler et al, 2002).…”
Section: Discussionmentioning
confidence: 99%